The effects of beetroot formula as an ergogenic aid on recreational runners - Sia, Isabella Beatrice T.
With the growing popularity of outdoor fitness activities among Filipinos, beetroot supplementation has gained attention for its potential to enhance endurance through increased nitric oxide (NO) production. This study aimed to investigate its effects on recreational runners during a 3000-meter time trial. Using a placebo-controlled, double-blind, crossover design, 20 runners (aged 20–29) completed trials under both beetroot and placebo conditions, with supplementation administered 2 to 2.5 hours before testing. Key outcomes included changes in blood lactate levels, heart rate recovery, and ratings of perceived exertion (RPE). Data normality was assessed using the Shapiro-Wilk test, followed by paired t-tests for pre- and post-test comparisons and repeated measures ANOVA for between-group analysis. Effect sizes were calculated using Cohen’s d, with significance set at α = 0.05. Statistical results suggested no significant differences between supplementation conditions, indicating that beetroot supplementation did not notably affect blood lactate levels (p = 0.931), heart rate (p = 0.381), time-trial performance (p = 0.246), and rate of perceived exertion (p < 0.001). In conclusion, consuming beetroot supplements 2 to 2.5 hours before running did not improve performance or physiological markers during 3000-meter runs.